PROPUESTA DE CREACIÓN DE UN RÉGIMEN ESPECIAL EN EL INSTITUTO ECUATORIANO DE SEGURIDAD SOCIAL PARA CUBRIR LAS PRESTACIONES Y BENEFICIOS DE LOS COMERCIANTES DE LOS CENTROS DE ABASTOS Y MERCADOS DE LA CIUDAD DE LOJA, PARA EL PERIODO 2013 - Elizalde Maurad, Milton Rolando (2016)
This investigation examines and analyzes Social Security as inalienable right to all workers regardless of their employment status with an emphasis on an important economic sector such as merchants and supplies and markets centres awarded; due to their conditions of vulnerability that currently are. Why this investigative work has been developed in order to contribute to the solution of a social problem that is present among traders of supplies and markets centres. Through a survey of retailers found that most of them are not affiliated to the social security, many of them are likely to suffer accidents at work, and its condition are vulnerable is so it suggests the importance of the creation of a special Social security scheme so that it covers the features and benefits for this sector of the economy. This study has developed it in four paragraphs describing a brief history of social security its history in our country, also is a description of the six markets that exist in the city of Loja, where also is an analysis socio-economic traders, then becomes a study of the different types of occupational risk that traders may have at the time of its commercial activity. Finally articulated content presents the solution to this problem.